Perovskite-WS2 Nanosheet Composite Optical Absorbers on Graphene as High-Performance Phototransistors - Zhang, Dan-Dan; Yu, Rong-Mei (Frontiers in Chemistry, 2019)
High-responsivity phototransis-tors with a structure of perov-skite-WS2 nanosheet composite optical absorber and a reduced graphene oxide (rGO) channel layer is demonstrated via a facile and low-cost solution-processing method. The WS2 nanosheets are dispersed within the perovskite matrix, forming the perovskite-WS2 bulk heterojunction (BHJ). The hybrid phototransistor exhib-its excellent figures of merit in-cluding high photoresponsivity of 678.8 A/W, high specific de-tectivity of 4.99×1011 Jones, high EQE value of 2.04×105 % and rapid response to photoswitching. The high photoresponsivity could be attributed to the WS2 nanosheets induced photo-generated electron-hole separa-tion promotion effects due to the selective electron trapping effects in the WS2 nanosheets, as well as the high carrier mobility of the rGO channel layer. This work provides a promising platform for constructing high-responsivity photodetectors.